Comparative study of the growth characteristics and electrical properties of atomic-layer-deposited HfO2 films obtained from metal halide and amide precursors. Issue 27 (29th June 2018) - Oh, Il-Kwon; Park, Bo-Eun; Seo, Seunggi; Yeo, Byung Chul; Tanskanen, Jukka; Lee, Han-Bo-Ram; Kim, Woo-Hee; Kim, Hyungjun
Abstract : Theoretical and experimental studies were performed on surface reactions during film growth and electrical properties of HfO2 using two different Hf precursors, HfCl4 and Hf(N(CH3 )2 )4 . Abstract : Downscaling of complementary metal-oxide semiconductor (CMOS) gate stacks requires the introduction of ultra-thin and high- k dielectrics such as HfO2 . Atomic layer deposition (ALD) is an excellent technique for producing high-quality high- k films. During ALD, chemical reactions on the substrate surface involve multiple processes that affect the chemical and electrical properties of the deposited films. Thus, the choice of an appropriate precursor for ALD is critical for obtaining high-quality high- k films, leading to good device performance. The aim of this study is to understand the surface reactions during the film growth along with the evaluation of the electrical properties of HfO2 deposited using two different Hf precursors, HfCl4 and Hf(N(CH3 )2 )4 . The growth behavior and electrical performance of ALD HfO2 thin films obtained using the two Hf precursors and H2 O as an oxidant at 250 °C are studied comparatively and discussed as a function of the process parameters, together with surface-reaction energetics determined by the density functional theory. Compared to Hf(N(CH3 )2 )4, the HfCl4 shows unfavorable nucleation behavior on the starting Si–OH surfaces. In addition, a more stoichiometric HfO2 film results from HfCl4 owing to its high reactivity, leading to lower leakage currents of Si-based devices than that of the film obtained from Hf(N(CH3 )2 )4 . Further, HfCl4 showed better nucleation on a 2D graphene substrate, leading to superior electrical performance in graphene-based field effect transistors. These results provide practical insights on selecting a suitable Hf precursor for producing gate dielectric layers for future nanoelectronics.